A comparison of input devices in elemental pointing and dragging tasks - Sellen, Abigail; Buxton, Bill (Proceedings of SIGCHI '91, New Orleans, LA., 1991)
An experiment is described comparing three devices (a mouse, a trackball, and a stylus with tablet) in the performance of pointing and dragging tasks. During pointing, movement times were shorter and error rates were lower than during dragging. It is shown that Fitts' law can model both tasks, and that within devices the index of performance is higher when pointing that when dragging. Device difference also appeared. The stylus displayed a higher rate of information processing than the mouse during pointing but not during dragging. The trackball ranked third for both tasks.
Top digital download from ACM Digital Library, April 2006